Empowering Future Biology Teachers: Integrating STEM and Design Thinking for Effective Sustainability Learning - Pamungkas, Rahmania; Suwono, Hadi; Ibrohim; Subiantoro, Agung Wijaya (SEAMEO QITEP in Science, 2025)
This study examines the implementation of a design project in a preservice biology teacher education course titled